PERTEMUAN SABAR DAN SYUKUR DALAM HATI - Sagir, Akhmad (Faculty of Ushuluddin and Humanities, 2014)
Gratitude and patience are two characters/attitudes that exists in every human being, there is one among us has misunderstanding and misinterpret on both the characters/attitudes. When both are brought into the real of social reality filled with romance and the problems of life. It is commonplace to understand that patience and gratitude are opposite attitude, both appears motivated by different circumstances. Patience usually will come out when someone gets something terrible that makes him uncomfortable. Instead of gratitude will occur if something comes to him to make him happy, excited and others for instance. This paper attempts to analyze both cases and meeting between both of characters/attitudes are in the heart of every human being.